Expert consensus on microtransplant for acute myeloid leukemia in elderly patients -report from the international microtransplant interest group. Issue 4 (April 2023) - Ai, Huisheng; Chao, Nelson J.; Rizzieri, David A.; Huang, Xiaojun; Spitzer, Thomas R.; Wang, Jianxiang; Guo, Mei; Keating, Armand; Krakow, Elizabeth F.; Blaise, Didier; Ma, Jun; Wu, Depei; et al.
Abstract: Recent studies have shown that microtransplant (MST) could improve outcome of patients with elderly acute myeloid leukemia (EAML). To further standardize the MST therapy and improve outcomes in EAML patients, based on analysis of the literature on MST, especially MST with EAML from January 1st, 2011 to November 30th, 2022, the International Microtransplant Interest Group provides recommendations and considerations for MST in the treatment of EAML. Four major issues related to MST for treating EAML were addressed: therapeutic principle of MST (1), candidates for MST (2), induction chemotherapy regimens (3), and post-remission therapy based on MST (4). Others included donor screening, infusion of donor cells, laboratory examinations, and complications of treatment.